THE INFLUENCE OF PARENTS' EDUCATION LEVEL ON STUDENT LEARNING OUTCOMES IN ONLINE LEARNING at SD DARUSSALAM KARANGDORO - Qurani, Qorinil; Junaidi, Muhammad (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2023)
This research was conducted at SD Darussalam Karangdoro which aims to answer the problems, 1) How is the basic education level of parents of grade1 students of SD Darussalam Karangdoro on the average student learning outcomes? 2) How is the secondary education level of parents of grade1 students of SD Darussalam Karangdoro on the average student learning outcomes? 3) How is the level of higher education of parents of grade1 students of SD Darussalam Karangdoro on the average student learning outcomes? 4) Is there any influence of parental education on student learning outcomes in online learning in the era of the covid-19 pandemic for grade 1 students at SD Darussalam Karangdoro for the 2020/2021 school year. The approach used is a quantitative approach and the type of survey research data collection techniques using observation, questionnaires, interviews, and documentation. The data analysis technique used One way Anova statistic with a significance level of 5%. The results of this study indicate: 1) The level of basic education of parents of grade 1 students at SD Darussalam Karangdoro from 24 respondents affects the average student learning outcomes of 46.17% in the fairly high category 2) The secondary education level of parents of grade 1 students at SD Darussalam Karangdoro from 19 respondents affects the average student learning outcomes of 54.79% were categorized as high enough. 3) the level of higher education of parents of grade 1 elementary school students Darussalam Karangdoro form 29 respondents, affected the average student learning outcomes of 63.32% in the high category 4) Based on the results of data analysis and hypothesis testing with the Anova statistical test, the P Value = 0.000, thus the significance level = 0.05 we reject Ho. So it can be concluded that the level of parental education has an effect on student learning outcomes in online learning.